Genetic Association of FERMT2, HLA-DRB1, CD2AP, and PTK2B Polymorphisms With Alzheimer’s Disease Risk in the Southern Chinese Population - Yan, Yi; Zhao, Aonan; Qui, Yinghui; Li, Yuanyuan; Yan, Ran; Wang, Ying; Xu, Wei; Deng, Yulei (Frontiers in Aging Neuroscience, 2020)
Objectives: This study aimed to explore the relationship between 18 single nucleotide polymorphisms (SNPs) and Alzheimer’s disease (AD) within the southern Chinese population. Methods: A total of 420 participants, consisting of 215 AD patients and 205 sex- and age-matched controls, were recruited. The SNaPshot technique and polymer chain reaction (PCR) were used to detect the 18 SNPs. Combined with the apolipoprotein E (APOE) ε4 allele and age at onset, we performed an association analysis between these SNPs and AD susceptibility. Furthermore, we analyzed SNP-associated gene expression using the expression quantitative trait loci analysis. Results: Our study found that rs17125924 of FERMT2 was associated with the risk of developing AD in the dominant (P=0.022, odds ratio [OR]=1.57, 95% confidence interval [CI]: 1.07–2.32) and overdominant (P=0.005, OR=1.76, 95% CI: 1.18–2.61) models. Moreover, compared with APOE ε4 non-carriers, the frequency of the G-allele at rs17125924 was significantly higher among AD patients in APOE ε4 allele carriers (P=0.029). The rs9271058 of HLA-DRB1 (dominant, overdominant, and additive models), rs9473117 of CD2AP (dominant and additive models), and rs73223431 of PTK2B (dominant, overdominant, and additive models) were associated with early-onset AD (EOAD). Using the genotype-tissue expression (GTEx) and Braineac database, we found a significant association between rs9271058 genotypes and HLA-DRB1 expression levels, while the CC genotype at rs9473117 and the TT genotype of rs73223431 increased CD2AP and PTK2B gene expression, respectively. Conclusions: Our study identifies the G-allele at rs17125924 as a risk factor for developing AD, especially in APOE ε4 carriers. In addition, we found that rs9271058 of HLA-DRB1, rs9473117 of CD2AP and rs73223431 of PTK2B were associated with EOAD. Further studies with larger sample sizes are needed to confirm our results.